Low-load Efficiency Improvement of a Three-Phase Bidirectional Isolated DC-DC Converter (3P-BIDC) Via Enhanced Switching Strategy - S. Mohd Sharifuddin, N.; M. L. Tana, N.; Akagi, H. (International Journal of Engineering and Technology, 2018)
This paper presents the system design, operation and enhanced switching strategy of a three-phase bidirectional isolated dc-dc converter (3P-BIDC). The paper discusses the operating modes of the 3P-BIDC using phase-shift modulation (PSM), with analysis on its soft-switching characteristics. The phase-shift modulation is the simplest modulation technique that can be applied to the 3P-BIDC. However, it comes with the consequences of low efficiency performance in the low-load conditions. Therefore, this paper investigates the improvement in efficiency of the 3P-BIDC during low-load condition using an enhanced switching strategy combining burst-mode switching and phase-shift modulation. The model of a 700-V, 100-kW, 20-kHz 3P-BIDC and the enhanced switching strategy are verified via simulation using PSCAD. The simulation results shows that the combination of burst-mode and phase-shift modulation technique improves the efficiency of the 3P-BIDC at low-load conditions. Â Â